2019
DOI: 10.1152/ajprenal.00455.2018
|View full text |Cite
|
Sign up to set email alerts
|

MST3 is involved in ENaC-mediated hypertension

Abstract: Liddle syndrome is an inherited form of human hypertension caused by increasing epithelial Na+ channel (ENaC) expression. Increased Na+ retention through ENaC with subsequent volume expansion causes hypertension. In addition to ENaC, the Na+-K+-Cl− cotransporter (NKCC) and Na+-Cl− symporter (NCC) are responsible for Na+ reabsorption in the kidneys. Several Na+ transporters are evolutionarily regulated by the Ste20 kinase family. Ste20-related proline/alanine-rich kinase and oxidative stress-responsive kinase-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Coordination of fluid accumulation, membrane delivery, cell proliferation and apoptosis is required for epithelial polarization and cyst and tubule formation. Among the diverse roles of MST3, we have defined its roles in the regulation of renal ion channels to maintain stable blood pressure [ 18 , 19 , 28 ], cell apoptosis [ 16 ] and cell migration [ 17 ]. These functions of MST3 are all involved in cell polarity and cyst formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coordination of fluid accumulation, membrane delivery, cell proliferation and apoptosis is required for epithelial polarization and cyst and tubule formation. Among the diverse roles of MST3, we have defined its roles in the regulation of renal ion channels to maintain stable blood pressure [ 18 , 19 , 28 ], cell apoptosis [ 16 ] and cell migration [ 17 ]. These functions of MST3 are all involved in cell polarity and cyst formation.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, our study showed that MST3 localized at the subapical site and cytosol of the renal tubules [ 18 , 19 ]. Although the MST3 knockdown mice exhibited normal renal tubule morphology, more ENaC was present at apical sites than in WT mice, indicating that MST3 inhibited ENaC expression at apical sites in the kidney [ 18 ]. Here, we found that overexpressed MST3 localized close to the basal membrane instead of the subapical membrane of cysts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mammalian Ste20-like protein kinase 3 (MST3/STK24) is mainly expressed in the thick ascending tubule, and at lower levels in the distal convoluted tubules. Hypomorphic mice for this protein kinase exhibited higher ENaC activity causing hypernatremia and hypertension [49]. In response to K þ loading, these maintained Na þ /K þ homeostasis by regulation of WNK4 expression thereby enhancing Na þ retention through increased NKCC2 and ENaC activity [50].…”
Section: Selected Recent Regulators Of Epithelial Sodium Channel Func...mentioning
confidence: 99%